Head Injuries in School-Age Children Who Play Golf. (April 2016) - Reuter-Rice, Karin; Krebs, Madelyn; Eads, Julia K.
Traumatic brain injury (TBI) is the leading cause of death and disability in children. We conducted a prospective study, which examined injury characteristics and outcomes of school-age children of 5.0–15.0 years ( N = 10) who were admitted to hospital for a TBI. This study evaluated the role of age, gender, the Glasgow Coma Scale, mechanisms and severity of injury, and functional outcomes. Seventy percent of the children sustained a TBI from a fall. We also found that playing golf was associated with 40% of the TBIs, with three (30%) children being unrestrained passengers in a moving golf cart and another one (10%) was struck by a golf club. Injury awareness could have benefited or prevented most injuries, and school nurses are in the best position to provide preventative practice education. In golf-centric communities, prevention of golf-related injuries should include education within the schools.